A novel dual fixation method for improving the reliable assessment of pulmonary vascular morphology in pulmonary hypertension rats - Yan Xu; Pu Liao; Xinyu Song; Wenchuan Guo; Bingxun Liu; Tong Ye; Ting Zhang; Rui Xiao; Liping Zhu; Yujun Shen; Yanjiang Xing; Jing Wang; et al. (Respiratory Research)
Abstract This study introduced a novel dual fixation method for the pulmonary vasculature and lung tissue in pulmonary hypertension (PH) rats, addressing the limitations of traditional fixation methods that failed to accurately preserve the in vivo status of pulmonary vascular morphology. The modified method involved a dual fixation process, combining individualized ventilation support and vascular perfusion to simulate the respiratory motion, pulmonary artery pressure and right ventricular output of the rat under in vivo conditions. Utilizing a monocrotaline-induced PH rat model, this study compared the dual fixation with the traditional immersion fixation, focusing on the quantitative assessment of alveolar expansion degree, capillary patency, endothelial cell quantity and wall thickness of pulmonary vein and artery. The results demonstrated that the dual fixation is superior in maintaining the authenticity and integrity of lung tissue and more sensitive in the evaluation of pulmonary artery hypertrophy, providing a more reliable representation of pulmonary vascular remodeling associated with PH.